SILARIANG DALAM PERSPEKTIF BUDAYA SIRI’ PADA SUKU MAKASSAR - Israpil Israpil (LP3M IAI Al-Qolam Malang, 2015)
Silariang or elopement is a social reality that is still happening in the tribal society of Makassar. Silariang is actually related withthe culture of siri '. This paper intends to reveal the causes and impacts silariang in Makassar tribe, which has negative implications mainly on the position of women in a family and society as a badge of honor (siri '). On the other hand, silariangp henomenon still occurs in Makassar tribe, although customs and traditions are very against it. The fact, that the cause of silariang in Makassar tribe is the economic factor, opposed matchmaking, social stratification, and the bad behavior of men. While the impact is strife within the family that led to the persecution, murder and moral sanctions. Even so,Silariang still occur, because the customary sanctions for offenders considered to be too mild, and well tolerance of the families who will receive back their son/daughter, known as maeabbaji (reconciliation).Keywords: Siri’, silariang, Makassar tribe.